Alcohol-Specific Mortality in People With Epilepsy: Cohort Studies in Two Independent Population-Based Datasets - Gorton, Hayley C.; Webb, Roger T.; Parisi, Rosa; Carr, Matthew J.; DelPozo-Banos, Marcos; Moriarty, Kieran J.; Pickrell, W. Owen; John, Ann; Ashcroft, Darren M. (Frontiers in Neurology, 2021)
Objectives The risk of dying by alcohol-specific causes in people with epilepsy has seldom been reported from population-based studies. We aimed to estimate the relative risk of alcohol-specific mortality in people with epilepsy, and the extent to which problematic alcohol use was previously identified in the patients’ medical records. Method We delineated cohort studies in two population-based datasets, the Clinical Practice Research Datalink (CPRD GOLD) in England (01/01/2001-31/03/2014) and the Secure Anonymised Information Linkage (SAIL) Databank in Wales (01/01/2001-12/31/2014), linked to hospitalisation and mortality records. People with epilepsy were matched to up to 20 persons without epilepsy on gender, age (+/- 2 years) and registered general practice. We identified alcohol-specific death from Office for National Statistics (ONS) records using specified ICD-10 codes. We further identified prescriptions, interventions and hospitalisations related to alcohol use. Results In the CPRD GOLD, we identified 9,871 individuals in the incident epilepsy cohort and 185,800 in the comparison cohort and, in the SAIL Databank, these numbers were 5,569 and 110,021, respectively. We identified a five-fold increased risk of alcohol-specific mortality in people with epilepsy versus those without the condition in our pooled estimate across the two datasets (deprivation-adjusted HR 4.85, 95%CI 3.46-6.79). Conclusion People with epilepsy are at increased risk of dying by an alcohol-specific cause than those without the disorder. It is plausible that serious alcohol misuse could either contribute to the development of epilepsy or it could commence subsequent to epilepsy being diagnosed. Regardless of the direction of the association, it is important that the risk of dying as a consequence of serious alcohol misuse is accurately quantified in people affected by epilepsy. These findings call for routine screening, identification and treatment, using the Alcohol Use Disorders Identification Test (AUDIT-C) in both primary and secondary care to detect alcohol consumption and misuse among people diagnosed with epilepsy.